Attitudes towards the employmentof disabled and changed capacity people in organizations - Dajnoki, Krisztina (Acta Scientiarum Socialium, 2011)
Attitudes towards the employment of disabled and changed capacity people in organizations We spend most of our lifetime working, so it is vital to have such a job which meets all of our expectations. Working this way contributes not only to the creation of our security feeling, but helps to realize ourselves. Moreover, considering the development of economy and society, it is important that we let people work and meet their individual needs through securing adequate number and quality positions. The disabled and changed capacity people, owing to their conditions, do not have the same skills, capacities as the healthy ones. The establishment of adequate conditions may contribute to their equal treatment and management. One of the most important challenges is that managers should understand a special point of view, by which workplaces play in an important role in the establishment of labour market (re)integration and approach of disabled and changed capacity people. This article, prepared in the framework of the research programme „Equal Opportuni-ty Human Resource Management – 4EM” introduces the most important benefits and drawbacks of the employment of disabled and changed capacity people. Results of the survey are supplemented by managerial interviews of the organisations examined.